A Quantitative Approach to Prioritize Sustainable Concrete - L. Sudheer Reddy; A. Suchith Reddy; S. Sunil Pratap Reddy (Civil Engineering Journal, 2019)
Cement industry consumes high energy and produces major emissions to the environment. In order to reduce the effects (environmental impact, energy, and resources) caused by conventional materials, various by-products and pozzolonic material are used to achieve sustainable concrete. Assessing the concrete performance based on multiple conflicting attributes is decisive and compelling. It is difficult to choose an alternative among the Supplementary Cementitious Materials (SCM) considering a set of quantitative performance attributes. Hence, the present study utilizes the theories of decision making to prioritize an alternative environmentally and technologically. The purpose of the present study is to observe the sustainable performance of five different concretes made of OPC, Fly ash, GGBS, Metakaolin and Composite Cement for a particular grade of concrete. The study has considered workability, strength attribute (compressive strength, split tensile and flexural strength) and durability attribute (Sorptivity and RCPT) at their respective optimum replacements. To prioritize an alternative material considering quantitative attributes, Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is utilized. From the results, it is observed that considering all attributes, flyash based concrete has higher performance and is prioritized among others. The developed approach facilitates the decision-makers in the selection of a sustainable alternative.